A new species of Arthrobrachus Solier, Arthrobrachus arquatus n. sp. (Coleoptera: Melyridae) from the South American Transition Zone, Argentina - Estrada, Patricia M. (Zootaxa, 2018)
A new species of Arthrobrachus Solier, A. arquatus n. sp. from Argentina, is described using external characters of the adult male and female including terminal segments of the abdomen and genitalia. Arthrobrachus arquatus n. sp. is morphologically close to A. tibialis Solier, 1849 from the Central Chile sub region, suggesting a phylogenetic connection. Comments on the possible origin of this relationship are made.